Evaluation of acute alterations in electrocardiographic parameters after cryoballoon ablation of atrial fibrillation and possible association with recurrence - (:unkn) unknown (TURKISH SOC CARDIOLOGY, 2021)
Objective: This study aimed to evaluate the acute effect of cryoballoon ablation (CB-A) on electrocardiographic parameters that have been suggested to reflect heterogeneity in atrial conduction and ventricular repolarization. Methods: A total of 67 patients (52.6 +/- 13.2 years, 43 men) without any exclusion criteria who had undergone CB-A for atrial fibrillation (AF) between January 01, 2015, and December 31, 2018, constituted our study population. Electrographic recordings obtained before and after the ablation procedure on the same day were retrospectively evaluated for the P-wave dispersion, QTc dispersion, Tp-Te interval, and Tp-Te/QT ratio. The pre- and post-ablation values were tested for significant differences. The association of the possible CB-A-related changes in these parameters with AF recurrence during follow-up was evaluated. Results: P dispersion (30.1 +/- 6.8 vs. 35.9 +/- 9.4 ms, p<0.001), QT dispersion (20.7 +/- 7.5 vs. 24.0 +/- 8.8 ms, p<0.001), Tp-Te duration (on V5 83.6 +/- 8.1 vs. 110.2 +/- 9.5 ms, p<0.001), and Tp-Te/QT ratio (on V5 0.22 +/- 0.03 vs. 0.28 +/- 0.02, p<0.001) were observed to increase significantly after CB-A. There was no association between the magnitudes of change in any parameter and AF recurrence. Conclusion: CB-A had significant effects on electrocardiographic parameters related to atrial conduction and ventricular repolarization in the acute phase after CB-A. Further prospective studies are required to examine the time-related course of these alterations and their impact on clinical outcomes.
Keywords: atrial fibrillation; catheter ablation; 12-lead electrocardiography; PULMONARY VEIN ISOLATION; CATHETER ABLATION; INTERVAL; PROLONGATION; RISK